Role of the kinetic chain in shoulder rehabilitation: does incorporating the trunk and lower limb into shoulder exercise regimes influence shoulder muscle recruitment patterns? Systematic review of electromyography studies. Issue 1 (22nd April 2020) - Richardson, Eleanor; Lewis, Jeremy S; Gibson, Jo; Morgan, Chris; Halaki, Mark; Ginn, Karen; Yeowell, Gillian
Abstract : Objective: To investigate the influence of trunk and lower limb motion on electromyography (EMG) muscle activity and recruitment patterns around the shoulder. Design: Systematic review. Data sources: MEDLINE, CINAHL, PEDro, AMED, PubMed, Cochrane Central Register of Controlled trials, Cochrane Database of Systematic reviews, SportsDiscuss and PROSPERO. Eligibility criteria: Studies investigating both multiregional kinetic chain (KC) shoulder exercises and localised non-kinetic chain (nKC) shoulder exercises in healthy subjects under the same experimental conditions were included in this review. Results: KC exercises produced greater EMG activation levels in 5 of 11 studies for the lower trapezius. Of the remaining studies, five found no difference between the exercise types and one favoured nKC exercises. KC exercises produced greater EMG activation levels in 5 of 11 studies for the serratus anterior. Of the remaining studies, three reported the opposite and three found no significant difference between the exercise types. nKC exercises produced greater EMG activation in infraspinatus in three of four studies. KC exercises produced the lowest trapezius muscle ratios in all studies. Studies investigating the upper trapezius, middle trapezius, supraspinatus, subscapularis, biceps brachii, latifissimus dorsi, pectoralis major, deltoid, and trapezius and serratus anterior ratios showed inconsistency. Conclusion: This review found evidence that integrating the KC during shoulder rehabilitation may increase axioscapular muscle recruitment, produce lower trapezius muscle ratios and reduce the demands on the rotator cuff. Stepping appears preferable to squatting. PROSPERO registration number: CRD42015032557, 2015.